The assessment of changes of the results in the 30-second chair stand and 8-foot up-and-go tests within women over the age of sixty, participating in the gymnastics class. A pilot study - Zieliński, Wojciech; Celka, Roman; Wojtkowiak, Tadeusz; Adamczyk, Jan (Biospołeczne uwarunkowania uczestnictwa w kulturze fizycznej i zdrowotnej osób w różnym wieku, 2017)
The ageing process leads to irreversible changes within the functioning of the whole human organism. One of the problems which the seniors have to face is sarcopenia, that is a progressive loss of the skeletal muscles mass, which results in the loss of strength. Regularly performed physical exercises may significantly slow down this process and even cause muscle hypertrophy.A 13-week programme of the shaping gymnastic exercises has been drawn up to improve the strength of the lower body muscles. 25 women aged 60–81 took part in this programme. Strength of the lower limbs and dynamic agility have been assessed relying on the 30-second chair stand and 8-foot up-and-go Fullerton tests.The results of the statistical analysis indicate the growth of strength of the lower muscles on average by 24% and the dynamic agility by 6%. The improved muscle persistence has also been observed – at the end of the cycle of research the group has achieved better results in the postworkout attempts than in the pre-workout ones.The shaping gymnastic exercises regularly performed by women over the age of sixty improve the strength of lower limb muscles, dynamic agility and muscle persistence.